G125 Primary and Secondary Care Multi-Site Audit of NICE Guidance on Urinary Tract Infections in Children. (4th June 2013) - Platt, C; Gyorffy, G; Dudley, J; Banerjee, J; McNulty, C; Larcombe, J; Jadresic, L
Abstract : Aims: Children and families should expect to receive NICE compliant care before and after diagnosis of UTI and independently of where this diagnosis is made. We aim to highlight the challenges faced by different healthcare providers in the diagnosis and management of children with UTI by evaluating the implementation of key aspects of the 2007 NICE guidance across primary and secondary care. We report on the findings of this national multi-site health quality improvement partnership (HQIP) project. Methods: Retrospective audit of 900 consecutive children <16 years based in 4 areas across the UK. 4 secondary care providers and 10 GP centres representing a diverse patient group were involved. 7 criteria based on 3 key NICE priorities (improving diagnosis, improving clinical evaluation and providing guidance in follow up after diagnosis) were audited in total with a standard of 100% compliance set for each. Results: Through a manual search of health and microbiology records, data was collected over a period of 12 months in 2010 on 1018 children. Testing for UTI within the recommended time frame in cases of unexplained fever in children <3 years was poor (35% of cases in secondary care, 34% of cases in primary care). Only 52% of infants <3 months were treated appropriately with parenteral antibiotics. Recording of salient points in the history of children with suspected UTI was poor. Follow up investigations were organised appropriately in only 46% and 55% of cases from primary and secondary care respectively. Urinary dipstick testing as a first line strategy for diagnosis was performed relatively well in 67% and 75% of confirmed UTI cases in primary and secondary care respectively. 84% of infants <3 months with suspected UTI were referred appropriately to specialist services. Conclusions: This audit has highlighted areas of weakness in the management of children with UTI, in particular, accuracy of diagnosis in children <3 years and the recording of historical features that differentiate typical and atypical UTI. Our enhanced awareness of best practise will improve the outcomes for children with UTI in the long term.